Keamanan Informasi dan Privasi Pengguna dalam Layanan Perpustakaan Digital - Putri, Cindy Amelia; Anwar, Rully Khairul; Amar, Siti Chaerani Djen; Rukmana, Evi Nursanti (Media Pustakawan, 2024)
The development of libraries from conventional to digital-based libraries has brought significant impacts on the way library services are provided and accessed by users. However, along with its benefits, digital libraries face new challenges related to data security and user privacy such as effective protection of personal data. This research aims to analyze security and privacy threats in digital library services and identify the implementation of security technologies and privacy policies in this context. This research uses the narrative literature review method to analyze 12 references relevant to the topic of information security and user privacy in digital library services. This research has security and privacy risks involved in digital library services, how security technologies are implemented, and how privacy regulations and policies impact the situation. Results show that virus attacks and brute force attacks are some of the security threats of digital libraries. To protect sensitive user data, the use of security technologies such as data encryption and the use of firewalls are also very important. Privacy regulations and policies such as GDPR go a long way in helping digital libraries maintain the privacy of their users. This analysis enhances our understanding of the problems and solutions in data security management and user privacy in digital library services. Thus, this research highlights the importance of managing information security and user privacy in the context of digital library services to ensure optimal protection of sensitive user data.